Peningkatan Kemampuan Mengelola Arsip Keluarga di Kalangan Penggerak PKK Kelurahan Sukomulyo Kabupaten Lamongan : Pengabdian - Faisal Fahmi; Zulfatun Sofiyani; Meinia Prasyesti Kurniasari; Endang Gunarti; Ajeng Mustika Pratiwi; Muhammad Namirus Salim (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The lack of public understanding and awareness in managing family archives in everyday life causes the archives to become damaged, not easy to find, and even lost. Many families ignore the importance of managing family archives, and understanding the contents of the information in archives so that they can be used as valid legal evidence of a family's life. The research aims to improve the community's ability to manage family records (KTP, KK, Deeds, Diplomas, Land/Building Certificates, and other securities) through the PKK drive. The research population involved PKK cadres in Sukomulyo subdistrict, Lamongan subdistrict, Lamongan regency. The training method is carried out by preparing, implementing and evaluating. Data was collected through pretest and posttest to measure the knowledge and skills of PKK activists. The analysis was carried out by looking at the pretest and posttest results to find out how significant the increase in knowledgeability (78.6%) and skills (57.1%) was in implementing the training material taught. The training succeeded in increasing knowledge, understanding, and skills in managing archives by classifying them and implementing a preservation process with encapsulation.